Serological Prevalence of Contagious Bovine Pleuropneumonia in Niger in 2017 - Yansambou, Mahamadou Seyni; Diallo, Alpha Amadou; Idi, Moumouni; Gagara, Haladou; Haido, Abdoul Malick; Bada Alambedji, Rianatou (Frontiers in Veterinary Science, 2018)
Contagious bovine pleuropneumonie (CBPP) is a highly contagious disease of cattle caused by Mycoplasma mycoides subsp. mycoides Biotype Small Colony (MmmSC). The disease currently occurs in most of sub-Saharan Africa and where it is endemic and a major constraint for improving pastoral productivity. Following the persistence of this scourge, and in order to control this disease, a serological survey was conducted to determine the prevalence of CBPP in Niger. In fact, 1590 sera were collected following a stratified sampling plan based on the risk factor of dissemination of CBPP. The analysis were performed at the Central Livestock Laboratory using the c-Elisa test. The results obtained show a wide distribution of the disease with an overall prevalence of 4.15% at individual level. The highest prevalence’s were recorded in the South-East regions (Zinder (7.5%), Diffa (7.5%)) and the West part (Tahoua (6.9%)). The prevalence at the commune level was about 36.55%, which was relatively high. The prevalence at strata level was 36.55% (95% PI 0.2428-0.4882). The expected prevalence’s did not match those found. The results of this serological survey are considered the reference situation of CBPP in Niger with the PRAPS project, and allowed to the country to redefine control policies for better control of the disease at national and sub-regional level.